2015
DOI: 10.1248/cpb.c15-00077
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkyl Chain Length and Unsaturation of the Phospholipid on the Physicochemical Properties of Lipid Nanoparticles

Abstract: Previously, we developed lipid nanoparticles (LNs) containing poorly water-soluble drugs using two types of phospholipids, a neutral phospholipid (hydrogenated soybean phosphatidylcholine) and a negativelycharged phospholipid (dipalmitoylphosphatidylglycerol), with mean particle sizes of less than 100 nm. Here, we studied the effects of alkyl chain length and unsaturation of neutral and negatively-charged phospholipids on the physicochemical properties of LNs. Three neutral phospholipids, dimyristoylphosphatid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 15 publications
(17 reference statements)
1
18
0
Order By: Relevance
“…NI-LNs made with DMPC had substantially smaller mean particle size and bigger PDI relative to other the particles (Table 8). Previously, it was reported that the size distribution had bimodal peaks, and that NI crystal precipitated one month after preparation [48]; thus, NI-LNs using DMPC had different properties from the other particles. Longer alkyl chain lengths result in higher phase transition temperatures and stronger van der Waals interactions.…”
Section: Resultsmentioning
confidence: 99%
“…NI-LNs made with DMPC had substantially smaller mean particle size and bigger PDI relative to other the particles (Table 8). Previously, it was reported that the size distribution had bimodal peaks, and that NI crystal precipitated one month after preparation [48]; thus, NI-LNs using DMPC had different properties from the other particles. Longer alkyl chain lengths result in higher phase transition temperatures and stronger van der Waals interactions.…”
Section: Resultsmentioning
confidence: 99%
“…For example, currently on the market there are two liposomal formulations of doxorubicin which differ in terms of the main component: Doxil is prepared mainly from HSPC and Lipo-Dox is prepared from DSPC. It was shown that lipid nanoparticles with longer acyl chain lipids show greater stability [ 31 ]. Our observations showed that replacement of 15 mol % HSPC with DSPC resulted in a significant increase not only in the stability of our preparations, but also in the increase of the efficiency of encapsulation.…”
Section: Discussionmentioning
confidence: 99%
“…Cholesterol has been reported previously to affect liposomal encapsulation rates, and in addition to this, the unsaturated character of DOPC in O-1 liposomes may contribute to higher DTX entrapment due to decreased packing density of lipids, thereby providing more space for the loaded drug. 34,43 The lowest encapsulation efficiency was obtained with ACD-1 at 20% cholesterol content. This may be caused by interactions between hydrophobic tails of DSPE-PEG and phospholipids occupying potential drug-loading areas.…”
Section: -41mentioning
confidence: 99%